Targeting KRAS Mutant in Non-Small Cell Lung Cancer: Novel Insights Into Therapeutic Strategies - Désage, Anne-Laure; Léonce, Camille; Swalduz, Aurélie; Ortiz-Cuaran, Sandra (Frontiers in Oncology, 2022)
Although KRAS-activating mutations represent the most common oncogenic driver in non-small cell lung cancer (NSCLC), various attempts to inhibit KRAS failed in the past decade. KRAS mutations are associated with a poor prognosis and a poor response to standard therapeutic regimen. The recent development of new therapeutic agents (i.e., adagrasib, sotorasib) that target specifically KRAS G12C in its GDP-bound state has evidenced an unprecedented success in the treatment of this subgroup of patients. Despite providing pre-clinical and clinical efficacy, several mechanisms of acquired resistance to KRAS G12C inhibitors have been reported. In this setting, combined therapeutic strategies including inhibition of either SHP2, SOS1 or downstream effectors of KRAS G12C seem particularly interesting to overcome acquired resistance. In this review, we will discuss the novel therapeutic strategies targeting KRAS G12C and promising approaches of combined therapy to overcome acquired resistance to KRAS G12C inhibitors.